Development of Electronic Modules Based on STEM to Train Students' Creativity: Validity and Practicality Analysis - Melisa Melisa; Eko Susilowati; Dewi Dewantara (Universitas Lambung Mangkurat, 2021)
The STEM-based electronic module is a systematic presentation of learning materials to support students' independence with an approach in four fields of knowledge: science, technology, engineering, and mathematics. This study aims to describe the feasibility of this STEM-based electronic module to train students' creativity. The specific objectives of this study are to describe: (1) The validity of the STEM-based electronic physics module; and (2) The practicality of the STEM-based physics electronic module. The type of research was ADDIE, with the subject of the trial of 27 students at class X Science-1 in a public high school in Banjarmasin City, South Kalimantan, Indonesia. Data collection was obtained from observations, interviews, questionnaires, and tests. This research was analyzed qualitatively and quantitatively. The research results showed that: (1) the validity of the STEM-based electronic physics module was in a